2021
DOI: 10.4049/immunohorizons.2000093
|View full text |Cite
|
Sign up to set email alerts
|

TSC1 Suppresses Macrophage Necroptosis for the Control of Infection by Fungal Pathogen Candida albicans

Abstract: Candida albicans is the most common, opportunistic human fungal pathogen whose complex interplay with the host innate immune system remains incompletely understood. In this study, we revealed that infection macrophages with C. albicans triggers prominent cell death, which is largely attributed to the RIPK3/MLKL-mediated necroptosis. Our results further demonstrated that the TSC1-mTOR pathway plays a pivotal role in the control of macrophage necroptosis upon engaging the Dectin-1/2 and TLR-2/4 pathways through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
1
9
0
1
Order By: Relevance
“…It is possible that both the inflammatory cytokines and the nasal commensals work together to induce macrophage necroptosis in CRSwNP. Our recent studies revealed mTOR hyperactivation sensitized cells to necroptosis by promoting RIPK3 and MLKL expression in both intestinal epithelial cells and murine macrophages, 18 , 33 here we uncovered a positive role of mTOR in facilitating TNF-α and IFN-γ-induced cell death without affecting RIPK3 and MLKL protein abundance. However, the detailed mechanisms of how mTOR regulates this process need to be further elucidated.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…It is possible that both the inflammatory cytokines and the nasal commensals work together to induce macrophage necroptosis in CRSwNP. Our recent studies revealed mTOR hyperactivation sensitized cells to necroptosis by promoting RIPK3 and MLKL expression in both intestinal epithelial cells and murine macrophages, 18 , 33 here we uncovered a positive role of mTOR in facilitating TNF-α and IFN-γ-induced cell death without affecting RIPK3 and MLKL protein abundance. However, the detailed mechanisms of how mTOR regulates this process need to be further elucidated.…”
Section: Discussionsupporting
confidence: 53%
“…Our previous studies reported mTOR signaling can promote necroptosis in intestinal epithelial cells and murine macrophages upon induction by PAMPs or fungal pathogen. 18 , 33 We wondered whether mTOR also played a role in TNF-α and IFN-γ mediated necroptosis. Intriguingly, mTOR was greatly activated upon TNF-α plus IFN-γ treatment as evidenced by increased phosphorylation of the mTOR substrate S6 ( Figure 5D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory RCD depends on the release of damage-associated molecular pattern (DAMPs) and inflammatory mediators 28 . RCD is increasingly understood to benefit the host 29 , and C. albicans is known to induce inflammatory RCDs, such as necroptosis, and pyroptosis to promote inflammation 30,31 . Indeed, deficiencies in these pathways accelerate disease progression during fungal infection 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…RCD is increasingly understood to benefit the host 29 , and C. albicans is known to induce inflammatory RCDs, such as necroptosis, and pyroptosis to promote inflammation 30,31 . Indeed, deficiencies in these pathways accelerate disease progression during fungal infection 31,32 . However, excessive inflammation results in renal immunopathology during candidiasis suggesting that other mechanisms or RCDs fine-tune immunopathology and fungal control.…”
Section: Introductionmentioning
confidence: 99%